ANALISIS INDEKS KEPUASAN MASYARAKAT TERHADAP LAYANAN PUBLIK PADA PT. PLN (PERSERO) ULP MANNA - Tito Irwanto; Eno Pramino; Ahmad Soleh (Universitas Prof. Dr. Hazairin SH, 2021)
The purpose of this study is to determine the index of community satisfaction with public services at PT. PLN (Persero) ULP Manna. The analytical method used is Public Satisfaction Index based on the Regulation of the Minister of Administrative and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017 with 9 indicators, namely requirements, procedures, completion time, costs/rates, product specifications, types of services, executive competence, behavior implementer, handling complaints suggestions and inputs, facilities and infrastructure. Public Satisfaction Index on public services at PT. PLN (Persero) ULP Manna is 78.25 with the quality of service B with good criteria because it is in the conversion interval value range of 76.61 - 88.30. Facilities and infrastructure elements are the elements that get the highest average score, namely 3.31 with Good criteria, this is because PT. PLN (Persero) ULP Manna has provided good facilities and infrastructure in providing services to the community. The elements that received a poor score were the time for completion of services with an average value of 3.00 and the handling of complaints and suggestions with an average score of 3.04 with a poor rating because it was located in the interval value 2.60 - 3.064..